Interleukin-33 Ameliorates Murine Systemic Lupus Erythematosus and Is Associated with Induction of M2 Macrophage Polarisation and Regulatory T Cells - Mo Yin Mok; Ka Sin Law; Wing Yin Kong; Cai Yun Luo; Endale T. Asfaw; Kwok Wah Chan; Fang Ping Huang; Chak Sing Lau; Godfrey Chi Fung Chan (Karger Publishers, 2023)
The innate cytokine IL-33 is increasingly recognised to possess biological effects on various immune cells. We have previously demonstrated elevated serum level of soluble ST2 in patients with active systemic lupus erythematosus suggesting involvement of IL-33 and its receptor in the lupus pathogenesis. This study sought to examine the effect of exogenous IL-33 on disease activity of pre-disease lupus-prone mice and the underlying cellular mechanisms. Recombinant IL-33 was administered to MRL/lpr mice for 6 weeks, whereas control group received phosphate-buffered saline. IL-33-treated mice displayed less proteinuria, renal histological inflammatory changes, and had lower serum levels of pro-inflammatory cytokines including IL-6 and TNF-α. Renal tissue and splenic CD11b+ extracts showed features of M2 polarisation with elevated mRNA expression of Arg1, FIZZI, and reduced iNOS. These mice also had increased IL-13, ST2, Gata3, and Foxp3 mRNA expression in renal and splenic tissues. Kidneys of these mice displayed less CD11b+ infiltration, had downregulated MCP-1, and increased infiltration of Foxp3-expressing cells. Splenic CD4+ T cells showed increased ST2-expressing CD4+Foxp3+ population and reduced IFN-γ+ population. There were no differences in serum anti-dsDNA antibodies and renal C3 and IgG2a deposit in these mice. Exogenous IL-33 was found to ameliorate disease activity in lupus-prone mice with induction of M2 polarisation, Th2 response, and expansion of regulatory T cells. IL-33 likely orchestrated autoregulation of these cells through upregulation of ST2 expression.